A Rejoinder to Opuda and Arnold - Patrick Shannon; Jaqueline Edmondson (Journal of Research in Rural Education, 2003)
Shelley's Reading First experience continues. Since the time we submitted our original manuscript and agreed to participate in this exchange, the Pennsylvania Reading First Director notified her that the district was awarded a Reading First grant. This surprised Shelley because she had not revised her initial proposal according to the state's 15 concerns faxed to her after her rejection notice in November (see Apendix). In our most recent conversations with Shelley, she conveyed her excitement about being funded to expand the guided reading libraries in classrroms and to hire the reading coaches for classroom practice according to the district's version of the Ohio State Literacy Framework. We attribute this change in the district's grant status to one of two possibilities.